Using of Coating Technique by Inorganic Flame Retardants to Protect Civil and Industrial Foundations from Fires - Al-Mosawi, Ali I.; Mahmood, Abbas A.; Salaman, Ali J.; Alwash, Naser A. (Al-Khwarizmi Engineering Journal, 2011)
In the present research the flame retardancy to buildings and industrial foundations which are manufacturing from advanced polymeric composite material was increased by coating it with surface layer included flame retardant material. A(3mm) thick antimony tetroxide was used as a coated layer to retard and prevent the flame spread to the coating surface of polyester resin (SIROPOL 8340-PI) reinforced with hybrid fibers as a woven roving (°45-°0) consist of carbon and kevlar (49) fibers, and exposed it to direct flame generated from gas torch at temperature of (2000ºC), at different exposed distance (10,15,20mm)and study the rang of resistance for this layer and its ability to protect the under composite material . The result obtained from erosion test show an improvement to the resistance of the composite material to high temperature after addition of antimony tetroxide layer and this resistance increased with increasing the exposed distance of flame .